Predicting Organizational Commitment Through Job Satisfaction : Empirical Analysis Using the PLS-SEM Method - Hartini,; Aris, Affandy Agusman; Panjaitan, Maludin; Mattunruang, Andi Aris (Prabandhan: Indian Journal of Management, 2026)
Purpose : The present study focused on identifying the influence of quality of work life and professional competence on both job satisfaction and organizational commitment. Additionally, it investigated how the two variables indirectly affected organizational commitment through job satisfaction. Methodology : Using an ex-post facto method, this quantitative analysis was conducted in Makassar City, South Sulawesi. A total of 115 teachers from state elementary schools were selected as respondents using a simple random sampling method. The collected data were analyzed using path analysis with partial least squares (PLS) variance-based structural equation modeling (SEM) through the Smart PLS version 3.0 program. Findings : The results showed that the quality of work life positively influenced both job satisfaction and organizational commitment. Meanwhile, professional competence did not have a significant direct effect on organizational commitment. It was also observed that job satisfaction had a positive effect on organizational commitment. Additionally, the quality of work life and professional competence indirectly influenced organizational commitment through job satisfaction. Practical Implications : This research builds a model of job satisfaction in an educational environment through organizational commitment, professional competence, and quality of work life. Originality : Unlike prior research on organizational commitment in companies, this research focused on organizational commitment in teachers.